The Solution Of Riccati Type Differential Equation By Means Of Variable Order Variable Stepsize Backward Difference Method - Ahmad Fadly Nurullah Rasedee; Mohamed Suleiman; Ali Ahmadian; Zarina Bibi Ibrahim; Khairil Iskandar Othman; Abdumalik Rakhimov (International Scientific Publications and Consulting Services, 2024)
In this article a variable order variable step size technique in backwards difference form is used to solve nonlinear Riccati differential equations directly. The method proposed requires calculating the integration coefficients only once at the beginning, in contrast to current divided difference methods which calculate integration coefficients at every step change. Numerical results will show that the variable order variable step size technique reduces computational cost in terms of total steps without effecting accuracy.